A Interação Terapêutica em Intervenções com Universitários com Transtorno de Ansiedade Social - Garcia, Vagner Angelo (2015)
Abstract Many studies have been conducted to evaluate the roles of the therapist and the client in a therapeutic process. In this segment, this study aimed to analyze the behavioral analytic interventions in therapy sessions with students with social anxiety disorder (SAD). Twenty-two sessions of a therapeutic dyad were analyzed and categorized according to a system of behavior categorization (SiMCCIT). The behavior frequency and duration results were grouped into three stages of intervention: Early Stage (first three sessions), Development Stage (five intermediate sessions), and Closing Stage (final three sessions). Therapist flexibility was present in adapting the procedure according to the needs of each client. Aspects of the therapeutic interaction (highlighted by category analysis) showing the way to act with clients suffering from SAD were discussed.